SOLUTION: m(x)=6x-9 and k(x)=2-3x/6x Find and simplify: (m-k)(x) I think it starts off this way: (m-k)(x)=m(x)-k(x) = (6x-9)-(2-3x)/(6x) This is as far as I can get...can someon

Algebra ->  -> SOLUTION: m(x)=6x-9 and k(x)=2-3x/6x Find and simplify: (m-k)(x) I think it starts off this way: (m-k)(x)=m(x)-k(x) = (6x-9)-(2-3x)/(6x) This is as far as I can get...can someon      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Mathway solves algebra homework problems with step-by-step help!

 Question 372754: m(x)=6x-9 and k(x)=2-3x/6x Find and simplify: (m-k)(x) I think it starts off this way: (m-k)(x)=m(x)-k(x) = (6x-9)-(2-3x)/(6x) This is as far as I can get...can someone please walk me thru this step by step? I posted this earlier but I set the equation up incorrectly. Thank you.Found 2 solutions by Fombitz, solver91311:Answer by Fombitz(13828)   (Show Source): You can put this solution on YOUR website!Just like with fractions you need a common denominator. In this case, So then Answer by solver91311(18785)   (Show Source): You can put this solution on YOUR website! So far, perfect. The common denominator is , so: And that is all there is. John My calculator said it, I believe it, that settles it